Mathematical Connections Through Brain-Based Learning with Geogebra Assistance - Susilawati, Wati; Siti Nursalimah, Nia; Maryono, Iyon (KnE Social Sciences, 2024)
During the COVID-19 pandemic, it became a challenge for the world of education, all exposure to the implementation of learning was carried out online, however, adjusting the learning process required the readiness of students and teachers in the field of technological literacy. The purpose of writing this paper is: to analyse the ability of mathematical connections between students who carry out GeoGebra-assisted brain-based learning and conventional learning, viewed by gender. The research method used was a quasi-experimental design with a non-equivalent control group. The sample consisted of an experimental class and a control class which were not selected randomly but were selected homogeneously. The implementation was carried out at one of the state middle schools in Bandung, Indonesia. Class VIII-C consists of 30 students as an experimental class carrying out GeoGebra-assisted brain-based learning and class VIII-F consists of 28 students as a conventional class. The instrument used is a mathematical connection ability test. Data analysis using two-way ANOVA. Research results: There is a difference in the achievement of increasing the ability of mathematical connections between students in the experimental class and the conventional class. There is no difference in the achievement of increasing the ability to relate mathematics based on gender (male, female). The brain-based learning approach with the help of GeoGebra facilitates the process of construction, interaction, reflection, and easy-to-understand material, so as to improve students’ mathematical connection abilities. Keywords: Mathematical Connections, Brain-Based Learning, Geogebra Assistance